The great Mann : a novel - Lurie, Kyra Davis (Crown, 2025)
"In this poignant retelling of The Great Gatsby, set amongst L.A.'s Black elite, a young veteran finds his way post-war, pulled into a new world of tantalizing possibilities-and explosive tensions"--